Tác động của phát triển tài chính đến tăng trưởng kinh tế tại các quốc gia trong khối Liên minh châu Âu - Dương Thị Bình, Minh; Lê Thị, Mai (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
The objective of this paper is to evaluate the impact of the financial system on economic growth for a sample of 25 European Union countries during the 2004–2016 period. At the same time, the authors also divided countries into three main groups to examine how the level of national development (represented by per capita income) affects the relationship between financial development and economic growth. Using Pooled OLS Model, Fixed Effects Model, Random Effects Model and Generalized Least Square Model, this study focuses on the impact of financial development on economic growth in the European Union countries. Then, this study determines which factor in financial development is the best explanation for the economic growth in these countries. This research results indicated that there is a one-way relationship exists from financial development to economic growth and this relationship is stronger in low-income countries.